Public service motivation research: achievements, challenges, and future directions - Perry, James L.; Vandenabeele, Wouter (2015)
This article takes stock of public service motivation research to identify achievements, challenges, and an agenda for research to build on progress made since 1990. After enumerating achievements and challenges, the authors take stock of progress on extant proposals to strengthen research. In addition, several new proposals are offered, among them conducting more research on the disaggregated construct, developing grounded theory of public service motivation to understand contextual variations across cultures and political institutions, and improving current measures to better capture loyalty to governance regime as an institutional dimension of the public service motivation construct. - Reproduced.
Keywords: Motivation